Study on the mechanism of aluminum melt corrosion of Fe-SG series metals - Dongjie Liu; Jiaheng Lei; Ziyang Yan; Qingdong Zhang; Yuzhou Du; Chao Yang; Bailing Jiang (Journal of Materials Research and Technology)
This paper investigates the corrosion behavior of Fe-SG series metals with different graphite nodule counts to molten Al by using the ultrasonic vibration hot-dip aluminum experimental method. Fe-SG series metals to aluminum melt exhibited a much better corrosion resistance compared to H13 tool steel. As the graphite nodule count increases, the hot melting loss rate of Fe-SG series metals gradually decreases, indicating an improvement in corrosion resistance to aluminum melt. Scanning and EDS analysis of the samples after hot-dip aluminum testing revealed that the thickness of the product layer increased progressively with the extension of hot-dip aluminum time. Through the analysis of the structure and composition of the product layer, it was found that the corrosion products in H13 steel were composed of Fe2Al5 and FeAl3. In addition to the two phases, the product layer of the Fe-SG series metals also contained granularly distributed Fe–Al–Si intermetallic compounds within the Fe2Al5 phase. This resulted in a better corrosion resistance to aluminum melt.